(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
The article reflects the modern trends in the development of intercontinental economic relations. The global integral processes are reflected in national and regional policies, leading to the formation of corporate logistics systems in the directions of movement of transnational cargo flows, and the systemic interrelation of factors that determine the prerequisites for the formation of logistics systems is described.